Use of STEAM education elements and tools in primary school mathematics - Andriievska, Vira; Olefirenko, Nadiia; Gaidus, Andrii; Ponomarova, Nataliia (Annales Universitatis Paedagogicae Cracoviensis | Studia ad Didacticam Mathematicae Pertinentia, 2024)
The spread of personal IT devices among today’s schoolchildren and the unrestricted use of various gadgets explain the ideology of educational changes regarding the end-to-end application of information and communication technologies in the educational process. As part of the Ukrainian school’s modernization, the STEAM concept plays a unique role. It ensures the appropriate introduction of the latest technologies into educational practice, focused on the intensification of the educational process, improvement of the forms and methods of the organization of education, and the expansion of the range of practical implementation of the skills acquired by schoolchildren. The article shows how the introduction of elements of STEAM education during mathematical primary school lessons can be supported by using specialized STEAM tools to engage students’ cognitive activity. During the execution of STEAM projects, students master many types and forms, ways, methods, and techniques of communication implementation successfully used in further work in other disciplines and beyond the school. The article highlights the didactic possibilities of STEAM tools as instrumental support for using elements of STEAM education in teaching mathematics in primary school. Instrumental support plays a vital role in achieving positive results in implementing STEAM education, which provides the opportunity to implement inquiry-based learning and experimental activities for primary school students in mathematics lessons.